Vapor-liquid equilibrium of water-hydrogen mixtures: A review of experimental data and modeling with a Cubic-Plus-Association Equation-of-State - Joachim Moortgat (PLoS ONE, 2025)
Interest in subsurface hydrogen storage and geological hydrogen exploration has grown in recent years. These processes generally involve two-phase, multi-component species transport, e.g. for hydrogen and water, and require accurate phase behavior models under varying temperatures and pressures. We compile experimental data spanning 0–200 ∘ C and up to 400 bar, revealing non-ideal H 2 – H 2 O behavior, such as a non-monotonic solubility trend with temperature. To model vapor-liquid equilibrium (VLE) compositions, we use the Cubic-Plus-Association (CPA) equation-of-state (EoS), which effectively captures hydrogen bonding effects. A single temperature-dependent binary interaction coefficient allows accurate reproduction of experimental data across all phases. In contrast, the cubic Peng-Robinson (PR) EoS lacks key molecular interactions and performs poorly, especially for the vapor phase. We also provide a polynomial parameterization of VLE compositions for easy use by hydrogen energy stakeholders. Our results offer a robust framework for hydrogen storage modeling and practical applications.